Art Coloring Therapy terhadap Stres pada Anak Didik di Lembaga Pembinaan Khusu Anak I Palembang - Umami, Niken Khaira; Mawardah, Mutia (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2020)
This study aims to look at the effect of art therapy coloring on stress in students at the Palembang Special Class Development Institute. Participants in this study were 11 students of the Palembang First Class Special Development Institute, which were combined into one group, the experimental group. This study is an experimental study with a randomized one group design pretest posttest. The sampling technique used was purposive sampling. To measure the stress of students used the standard scale PSS-14 (Perceived Stress Scale-14) which consists of 14 questions about feelings and perceived conditions. Pretest the experimental group, participants were only given the same PSS-14 scale as they did the posttest. The data in this study were analyzed using paired t-test techniques, the results of the data analysis obtained a very significant effect of art therapy coloring on stress with a value of r = 0.001 (r <0.05 and r <0.01) and t value = 4.913 . Based on these results it can be concluded that art therapy coloring affects stress on students in the Special Class Development Board of Palembang.